2012
DOI: 10.1037/a0026679
|View full text |Cite
|
Sign up to set email alerts
|

Memory for emotionally arousing events over time in Autism Spectrum Disorder.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. In press with Emotion Permanent repository link:Memory for arousing events in ASD 2 AbstractEmotionally arousing events are typically better remembered and more resistant to forgetting than neutral events. Findings from word list paradigms suggest that this may not hold for individuals with Autism Spectrum Disorder (ASD), who also tend to be less accurate as eyewitnesses under some circumstanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 35 publications
3
31
1
Order By: Relevance
“…The greater increase in SBP reactivity is consistent with the increased perception of stress given high correlations between systolic blood pressure and perceived stress identified in extant literature (Manuck 1994; Cohen et al 2000). The remainder of the findings suggests that some aspects of biological stress response of adults with ASD is comparable to typical adult community volunteers (e.g., Maras & Bowler, 2012; Maras et al, 2012; Mathersul et al, 2013). However, of note, descriptive data adds to the body of research that indicates that individuals with ASD have resting heart rates that are significantly higher than typical community volunteers.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The greater increase in SBP reactivity is consistent with the increased perception of stress given high correlations between systolic blood pressure and perceived stress identified in extant literature (Manuck 1994; Cohen et al 2000). The remainder of the findings suggests that some aspects of biological stress response of adults with ASD is comparable to typical adult community volunteers (e.g., Maras & Bowler, 2012; Maras et al, 2012; Mathersul et al, 2013). However, of note, descriptive data adds to the body of research that indicates that individuals with ASD have resting heart rates that are significantly higher than typical community volunteers.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, adults with ASD experience more stress and anxiety than adults with intellectual disabilities (Gillott and Standen 2007). This research also identified associations between higher levels of perceived stress and lower levels of social functioning (Bishop-Fitzpatrick et al 2015), between higher levels of perceived stress and lower levels of quality of life (Hong et al 2016), and between higher levels of perceived stress and greater levels of autism symptomatology (Maras et al 2012). Taken together, this research on stress in ASD suggests that impaired stress mechanisms may be intrinsic deficits in ASD that have not been previously considered.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…It appears that delivering these instructions in the SAI format did not alleviate any difficulties caused by the reduced influence of emotion on memory in ASD (e.g., Deruelle, Hubert, Santos & Wicker, 2008;, but see Maras, Gaigg & Bowler, 2012). Further work is also needed to identify potential benefits of externally imposed subject foci that might act as scaffolding and, therefore, be supportive.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found evidence of an emotional enhancement of memory for emotional content as compared to neutral content for stimuli that range from words to pictures to videos (e.g., Budson, Todman, Chong, Adams, Kensinger, Krangel, & Wright, 2006; Charles, Mather, & Carstensen, 2003; Maras, Gaigg, & Bowler, 2012). Further, in some of these studies emotion increased false memory compared to nonemotional stimuli.…”
Section: Introductionmentioning
confidence: 99%